Strategic Governance Model for Strengthening Maritime Defense and Cultural Heritage Capacity on Penyengat Island: An Integrated SWOT–AHP Analysis - Ceppi Hilmansyah (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Indonesia’s maritime defense increasingly requires integrated governance approaches that extend beyond conventional military frameworks. Strategic small islands play an important role not only in territorial security but also in strengthening national resilience through cultural heritage and community-based governance. Penyengat Island in the Riau Islands Province represents a strategic location where maritime history, cultural heritage, and geopolitical significance converge. However, its potential has not been fully optimized within Indonesia’s non-military maritime defense system due to limitations in governance coordination and human resource capacity. This study aims to formulate priority governance strategies to strengthen Penyengat Island as a maritime defense and cultural heritage governance model. A mixed-methods approach was applied using SWOT analysis to identify strategic factors and the Analytical Hierarchy Process (AHP) to determine policy priorities. The results place Penyengat Island in Quadrant I (SO), indicating strong internal capabilities and significant external opportunities. AHP analysis identifies integrated maritime human resource development as the top priority, followed by strengthened intergovernmental governance and collaborative public–civil–military partnerships. These findings highlight the importance of human resource capacity and governance integration in optimizing the strategic role of small islands in Indonesia’s maritime defense system.